Allergen relative abundance in several wheat varieties as revealed via a targeted quantitative approach using MS. Issue 10 (May 2015) - Rogniaux, Hélène; Pavlovic, Marija; Lupi, Roberta; Lollier, Virginie; Joint, Mathilde; Mameri, Hamza; Denery, Sandra; Larré, Colette; Lüthje, Sabine; Deswal, Renu; Agrawal, Ganesh Kumar
<x xml:space="preserve">Abstract</x> Food allergy has become a major health issue in developed countries, therefore there is an urgent need to develop analytical methods able to detect and quantify with a good sensitivity and reliability some specific allergens in complex food matrices. In this paper, we present a targeted MS/MS approach to compare the relative abundance of the major recognized wheat allergens in the salt‐soluble (albumin/globulin) fraction of wheat grains. Twelve allergens were quantified in seven wheat varieties, selected from three Triticum species: T. aestivum (bread wheat), T. durum (durum wheat), and T. monococcum. The allergens were monitored from one or two proteotypic peptides and their relative abundance was deduced from the intensity of one fragment measured in MS/MS. Whereas the abundance of some of the targeted allergens was quite stable across the genotypes, others like alpha‐amylase inhibitors showed clear differences according to the wheat species, in accordance with the results of earlier functional studies. This study enriches the scarce knowledge available on allergens content in wheat genotypes, and brings new perspectives for food safety and plant breeding.